Soybean performance as affected by desiccation time of Urochloa ruziziensis and grazing pressures - Franchini, Julio; Balbinot Junior, Alvadi; Debiasi, Henrique; Conte, Osmar (Revista Ciência Agronômica, 2014)
Integrated crop-livestock farming system have demonstrated various economic and environmental advantages. However, there is lack of information on the effects of different desiccation times of Urochloa ruziziensis and grazing pressures on the soybean performance. This study aimed to evaluate the performance of three soybean cultivars, sown after different desiccation times of U. ruziziensis grazed at three heights during the 2012/13 growing season, in southern Brazil. The U. ruziziensis were continuously grazed for 6 months by 6, 4 and 2 animal units (AU) per hectare, leading to average pasture heights of 15; 35; and 50 cm, respectively. Each pasture height constituted a different experiment. The experiments were laid out using randomized complete block design (RCBD) with split-plot arrangement in four replications. The treatments consisted of four desiccation times (35; 28; 20; and 8 days before the soybean sowing), allocated in the main plots, and three soybean cultivars (Vmax RR; BMX Potência RR; and NA 5909 RR), distributed in the subplots. Increased interval between U. ruziziensis desiccation and soybean sowing resulted in higher soybean plant density and height, but the effects on soybean grain yields were not significant. The highest soybean grain yield was obtained when the pasture height was maintained in 35 cm, regardless of soybean cultivars. The performance of the three soybean cultivars was not influenced by the interaction between desiccation time and the pasture residue mass on the soil at soybean sowing, defined by the pasture height.